ANGKA BANDING NETROFIL/LIMFOSIT APENDISITIS AKUT - Yanty Tandirogang; Uleng Bahrun; Mutmainnah Mutmainnah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Acute appendicitis is one of the acute abdominal conditions encountered in almost all hospitals in Indonesia. Acute inflammation of the appendix requiring immediate surgery to prevent complications, so it should takes several particular checking's to support the diagnosis quickly. These are leukocytes count, especially neutrophils and lymphocytes as the sensitive marker of the inflammatory process which belong to the simple laboratory examination and can be used as a diagnostic marker of acute appendicitis as well. The inflammatory immune response can be described of the percentage of neutrophils to the lymphocytes ratio in the circulation. A retrospective study was performed on patients whom suspected for acute appendicitis those undergoing appendectomy from January 2010âˆ’May 2011. The data were grouped according to post appendectomy diagnosis and the ratio of neutrophils/lymphocytes (NLR) compared with other parameter. The NLR in each group was compaed by one way ANOVA analyzing. A total of 59 patients were identified: 19 catarrhally, 19 phlegmonous, 10 gangrenous and 11 with perforation. Compared with other markers, NLR is much better in predicting acute appendicitis. NLR increased in all groups (mean>7), specifically on the perforated appendicitis that is greatly increased (mean=12.273). But this was not significantly different NLR from the group (p=0.098). Based on this study it can be concluded, that NLR is the better marker for diagnosis rather than leukocyte and USG. But unfortunately, it can not be used to differentiate the grading in acute appendicitis.